Control of crystalline phase and morphology of calcium carbonate by electrolysis: Effects of current and temperature. Issue 11 (1st August 2019) - Miyazaki, Toshiki; Arii, Takashi; Shirosaki, Yuki
Abstract: Calcium carbonate (CaCO3 ) can show various properties related to its different crystalline phases and is therefore a useful material for various applications. Wet processes are known to be suitable for preparing metastable CaCO3 polymorphs. Electrolysis has been proposed as a preparation method at ambient conditions. Although several electrolytic approaches have been reported, the effects of the applied current and temperature of the electrolyte on the crystalline phase and morphology of CaCO3 remain unclear. In the present study, we attempted the electrochemical preparation of CaCO3 particles under various electrolysis conditions and discuss the mechanism of CaCO3 particle formation. The crystalline phases and morphologies of the CaCO3 precipitates markedly changed depending on the applied current and method of cooling the electrolyte. We assume that these factors were governed by the degree of change in temperature, supersaturation, and pH of the electrolyte that were induced by differences in the electrolysis current.